Convert the logarithmic equation to exponential form. log_{x}(64)=yThe base is AnswerThe exponent is AnswerThe result is Answer
![Convert the logarithmic equation to exponential form logx64yThe base is AnswerThe exponent is AnswerThe result is Answer class=](https://us-static.z-dn.net/files/ddd/38ddd2731d901dbb1ea1065b49a37285.png)
In order to convert the logarithm equation into an exponential equation, we can use the logarithm definition:
[tex]\log _ab=c\to a^c=b[/tex]So we have:
[tex]\begin{gathered} \log _x64=y \\ x^y=64 \end{gathered}[/tex]Therefore:
The base is x
The exponent is y.
The result is 64.